1993
DOI: 10.1063/1.108753
|View full text |Cite
|
Sign up to set email alerts
|

Large blue shift of light emitting porous silicon by boiling water treatment

Abstract: A boiling water treatment of light emitting porous silicon can give rise to a large blue shift of its photoluminescence spectrum and meanwhile strengthen the skeleton of porous Si by filling up many pores with aqueous oxide. A stable blue-green light emission at the peak wavelength down to 500 nm is achieved. FTIR measurements show that the formation of Si dihydride on the sidewall surfaces of the Si rods is not responsible to the visible luminescence for the very thin Si wires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(28 citation statements)
references
References 8 publications
0
26
0
2
Order By: Relevance
“…The result is very interesting since several papers attributed the photoluminescence from porous silicon to the amorphous silicon layer or to the presence of siloxene on the silicon surface. The blue luminescence from porous silicon has been generally obtained after a long dipping in Ethanol/H 2 O, chemical oxidation of anodized layer in HNO 3 [8,13,14] or after PS treatment in boiled water [15]. The origin of the blue luminescence band in the oxidized porous Si has to date not been convincingly established.…”
Section: Wavelength (Nm)mentioning
confidence: 99%
“…The result is very interesting since several papers attributed the photoluminescence from porous silicon to the amorphous silicon layer or to the presence of siloxene on the silicon surface. The blue luminescence from porous silicon has been generally obtained after a long dipping in Ethanol/H 2 O, chemical oxidation of anodized layer in HNO 3 [8,13,14] or after PS treatment in boiled water [15]. The origin of the blue luminescence band in the oxidized porous Si has to date not been convincingly established.…”
Section: Wavelength (Nm)mentioning
confidence: 99%
“…Prior to treatment with water, both lines were present in the spectrum, and decreased in intensity after boiling water was added. Instead a band appeared at 1105 cm −1 , showing that treatment with water had caused oxidation (Hou et al, 1993).…”
Section: Blue Fluorescencementioning
confidence: 99%
“…Hou and co-workers treated light-emitting porous silicon with boiling water (Hou et al, 1993) and observed a large blue shift in the fluorescence towards the green-blue spectral range. Infrared spectroscopy was performed with the specific goal to assess whether the formation of silicon monohydride (2080 cm −1 ) and silicon dihydride (2120 cm −1 ) was correlated with the appearance of blue fluorescence.…”
Section: Blue Fluorescencementioning
confidence: 99%
“…Some approaches, such as high temperature annealing [1], boiling-water treatment [2], ion implantation [3,4] etc., have been attempted in order to reduce the size of the silicon nanocrystals to further enlarge the band gap of Si and to increase the emission intensity. Ion implantation is one of the good candidates for nanocrystal formation due to its compatibility with Si device processes.…”
Section: Introductionmentioning
confidence: 99%